Utilization of fungal and bacterial bioremediation techniques for the treatment of toxic waste and biowaste - Thirumalaivasan, Natesan; Gnanasekaran, Lalitha; Kumar, Suresh; Durvasulu, Rajesh; Sundaram, Thanigaivel; Rajendran, Saravanan; Nangan, Senthilkumar; Kanagaraj, Kuppusamy (Frontiers in Materials, 2024)
The escalating accumulation of toxic wastes and biowastes constitutes a critical environmental crisis that demands immediate and effective solutions. Traditional waste treatment methods, predominantly chemical and physical, are increasingly viewed as unsustainable, burdened by high operational costs and the risk of generating secondary pollutants. Against this backdrop, bioremediation emerges as a crucial and sustainable alternative, utilizing the natural detoxifying capabilities of microorganisms. This review article focuses on the use of fungal and bacterial strategies in bioremediation, emphasizing their vital role in the degradation, stabilization, or detoxification of pollutants. We provide an in-depth analysis of the mechanisms by which fungi and bacteria break down various contaminants, presenting a current snapshot of the field’s state of knowledge. The article highlights recent innovative advancements that improve the effectiveness and expand the applicability of bioremediation technologies. Moreover, it discusses the practical challenges of scaling these solutions to meet global environmental needs and suggests directions for future research and implementation. This synthesis not only underscores the significance of microbial bioremediation in addressing pressing environmental problems but also acts as a call to action for continued innovation in the sustainable management of hazardous wastes.